The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/1478422x.2020.1721806
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of commonly used plumbing materials for water distribution systems exposed to disinfection treatments

Abstract: In this study, the corrosion resistance of commonly used plumbing materials was evaluated when three disinfection treatments were applied in hot water distribution systems. In particular copper, brass, stainless steel and galvanised steel were tested in environments containing monochloramine, chlorine dioxide and hydrogen peroxide disinfectants under real field conditions for a long period of time (1 year), in order to evaluate the effect of free corrosion on the metal specimens; chlorinated polyvinylchloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Several factors make hospital buildings suitable for colonization with bacteria and moulds: large and complex water systems with areas of low flow predispose to stagnation and biofilm formation and water temperatures optimal for healthcare use may also be ideal for bacterial growth [1]. Moreover, water characteristics, age and corrosion of the pipes, or metabolic activity of colonizing bacteria can influence the microbial community [2][3][4]. Therefore, the microbial ecology of water networks varies in the water distribution systems [5] and can serve as reservoirs for waterborne pathogens such as Legionella spp., Pseudomonas aeruginosa, Stenotrophomonas maltophilia, Acinetobacter spp., and non-tuberculous mycobacteria [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors make hospital buildings suitable for colonization with bacteria and moulds: large and complex water systems with areas of low flow predispose to stagnation and biofilm formation and water temperatures optimal for healthcare use may also be ideal for bacterial growth [1]. Moreover, water characteristics, age and corrosion of the pipes, or metabolic activity of colonizing bacteria can influence the microbial community [2][3][4]. Therefore, the microbial ecology of water networks varies in the water distribution systems [5] and can serve as reservoirs for waterborne pathogens such as Legionella spp., Pseudomonas aeruginosa, Stenotrophomonas maltophilia, Acinetobacter spp., and non-tuberculous mycobacteria [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…All these methods have proven effective against Legionella and other waterborne pathogens, but active concentrations of biocide need to be continuously monitored since no one eliminates the bacteria once the water network is contaminated [12,13,18,19]. The main disadvantages associated with chemical treatments are corrosiveness and, limited to chlorine-based biocides, formation of toxic disinfection by-products (DBPs) [3,12,13,20].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatives to chlorine such as chlorine dioxide, chloramines, ozone, and UV disinfection can be used. Chlorine and each of these disinfectants have different advantages and disadvantages in terms of cost, efficacy and stability, ease of application, pipe corrosion, and types of DBPs [ 8 , 9 ]. The DBPs of most concern include trihalomethanes (THMs) and haloacetic acids formed with chlorine, bromate formed during ozonation, and chlorite typically formed from chlorine dioxide treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Giovanardi et al (2020), when studying the corrosion of metallic materials commonly used in water distribution systems exposed to disinfection treatments with monochloramine, chlorine dioxide and hydrogen peroxide, found that galvanized steel parts showed greater thickness loss than stainless steel parts. These results were verified by analysing the cross sections of the samples under a stereomicroscope at 10× magnification, and in addition, the same authors reported the greater resistance to corrosion of the second material in relation to the first, which once again corroborates the results obtained in this study.…”
Section: Resultsmentioning
confidence: 99%